2019
DOI: 10.1016/j.jbspin.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Prealbumin, platelet factor 4 and S100A12 combination at baseline predicts good response to TNF alpha inhibitors in rheumatoid arthritis

Abstract: A multivariate model combining 3 biomarkers (prealbumin, platelet factor 4 and S100A12) accurately predicted response of RA patients to TNFi and has potential in a daily practice personalized treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“… 27 Similar to vitamin D, prealbumin and RBP4 are demonstrated to play an important role in the activity assessment and prognosis prediction of some inflammatory diseases. 17 , 28 , 29 Furthermore, previous study and our study indicated that the predictive capacity of prealbumin and RBP4 was likely superior to vitamin D in identifying endoscopic remission. 30 This suggests that prealbumin or RBP4 may be promising biomarkers with broad application in CD, and more research needs to be carried out.…”
Section: Discussionsupporting
confidence: 52%
“… 27 Similar to vitamin D, prealbumin and RBP4 are demonstrated to play an important role in the activity assessment and prognosis prediction of some inflammatory diseases. 17 , 28 , 29 Furthermore, previous study and our study indicated that the predictive capacity of prealbumin and RBP4 was likely superior to vitamin D in identifying endoscopic remission. 30 This suggests that prealbumin or RBP4 may be promising biomarkers with broad application in CD, and more research needs to be carried out.…”
Section: Discussionsupporting
confidence: 52%
“…In contradiction, Lopetusa et al found a lower rate of response to treatment and of disease remission in female patients under TNF inhibitors with axial spondyloarthritis[34]. As for possible explanations, Nguyen et al showed that the three biomarkers praealbumin, platelet factor 4 and S100A12 accurately predict the response of patients with rheumatoid arthritis to TNF inhibitors[35]. Further studies about a gender-specific correlation of these marker could reveal useful findings.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding albumin, the iTRAQ data revealed that albumin was elevated in the Rs group and was reduced in the NRs group; however, clinical data from this study revealed that the difference in ALB between the NRs and Rs group was not statistically significant, possibly owing to the mixture of four samples involved in iTRAQ analysis, which required further confirmation in more patients. Similarly, according to Nguyen, 21 a multivariate model that includes prealbumin can predict the response of patients with RA to TNF inhibitors. Therefore, the role of albumin in response mechanisms needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%